2003
DOI: 10.1073/pnas.2534397100
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-linked processes in cyanobacteria are as numerous as in chloroplasts, but targets are different

Abstract: Light-dependent regulation of a growing number of chloroplast enzymatic activities has been found to occur through the reversible reduction of intra-or intermolecular disulphides by thioredoxins. In cyanobacteria, despite their similarity to chloroplasts, no proteins have hitherto been shown to interact with thioredoxins, and the role of the cyanobacterial ferredoxin͞thioredoxin system has remained obscure. By using an immobilized cysteine 35-to-serine site-directed mutant of the Synechocystis sp. PCC 6803 thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
156
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(163 citation statements)
references
References 45 publications
(51 reference statements)
6
156
1
Order By: Relevance
“…In C. reinhardtii we found six potential targets involved in biosynthesis of arginine (argininosuccinate synthase), threonine (threonine synthase), lysine (diaminopimelate epimerase), branched amino acids valine and isoleucine (dihydroxyacid dehydratase and ketolacid reductoisomerase), and leucine (isopropylmalate dehydrogenase). Synechocystis argininosuccinate synthase (16) and Arabidopsis dihydroxyacid dehydratase (14) have already been proposed as TRX targets. The four other proteins are new targets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In C. reinhardtii we found six potential targets involved in biosynthesis of arginine (argininosuccinate synthase), threonine (threonine synthase), lysine (diaminopimelate epimerase), branched amino acids valine and isoleucine (dihydroxyacid dehydratase and ketolacid reductoisomerase), and leucine (isopropylmalate dehydrogenase). Synechocystis argininosuccinate synthase (16) and Arabidopsis dihydroxyacid dehydratase (14) have already been proposed as TRX targets. The four other proteins are new targets.…”
Section: Resultsmentioning
confidence: 99%
“…A single study was led with cyanobacteria and revealed targets mostly different from those of higher plants (16). The unicellular eukaryotic green alga Chlamydomonas reinhardtii possesses a TRX system in chloroplasts and cytosol (17) and very likely in mitochondria (3).…”
mentioning
confidence: 99%
“…Trxs are small, multifunctional, widely distributed redoxactive proteins operating through a reversible reduction of intra-or intermolecular disulfides Lindahl & Florencio, 2003). Recently, numerous putative Trx targets have been identified in plant chloroplasts (Balmer et al, 2003Marchand et al, 2004), in green algae (Lemaire et al, 2004) and in cyanobacteria (Lindahl & Florencio, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous putative Trx targets have been identified in plant chloroplasts (Balmer et al, 2003Marchand et al, 2004), in green algae (Lemaire et al, 2004) and in cyanobacteria (Lindahl & Florencio, 2003). About 200 proteins appear to be linked to Trx in plants (Buchanan & Balmer, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation